Kajian Penataan Saluran Drainase Berdasarkan Rencana Tata Guna Lahan Kota Kepanjen Kabupaten Malang - Cahyono, Dwi Adi; Masrevaniah, Aniek; Dwi Priyantoro, Dwi Priyantoro (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2013)
Kepanjen is the capital city of Malang regency which grows rapidly alongwith requirements of city need solution use that require special handling for a drainage system that can control the flood by utilizing the existing space. Using the data of year 1998, 2002, 2006, 2010, it is obtained the discharge plant for the year of 1998 was up to 41.812 m 3 /second, in 2002 was up to 50.230m 3 /second, in 2006 was up to 59.178 m /second, in 2010 was to 72.363 m 3 /second, from program analysis by minitab 16 Quadratic Trend Model obtained for 2022 are 124 m 3 /second discharge plan. To finish up the issues raised was done by normalization channel along 38.639 m = 38,6 km, create a new channel along 18.713 m = 18,7 km, load reduction along 615 m = 0,6 km, high rice channel planning along 15.872 m = 15,9 km, so 100% can reduce flood volume on each channel for the year 2022.Keyword : Land Use, To Plan Trend Debit, Flood Prevention